Resocializing values of sport - Kaźmierczak, Arkadiusz; Kowalska, Jolanta Elżbieta (Journal of Education, Health and Sport, 2018)
In the era of dynamic civilization changes, new pathological phenomena appear - alcoholism, drug addiction, demoralization and crime of children and youth, whose intensification is becoming one of the most serious threats to social life. The consequence of destructive phenomena is the changing model of upbringing, which is a natural response to the phenomenon of social maladjustment accompanying these changes together with the aggressive behavior. In the educational process, referring to the return of the student to the proper paths of social existence, sports activity plays an important role. It shapes the active lifestyle, affects the destruction of aggressive behavior, teaches fair play, honesty in personal life, cooperation and a friendly attitude towards other people . Research experiment carried out by many pedagogues shows that sport enables socially maladjusted people to fulfill different social roles, develops responsibility for entrusted tasks and opens the way to a normal life.